Positioning in News Translation Regarding Hamas: A Parallel Corpus-Based Approach - Ar Rusyfa, Imamati Zikra; Datang, Frans Asisi; Junaidi, Junaidi (Journal of Languages and Language Teaching, 2025)
Translating news reports can hardly be free from subjectivity, especially in relation to a conflict, since the opposing ideology often creates friction that necessitates translators to assume complex and multifaceted roles. The concept of positioning refers to participants’ attitudes or stances toward the event or other participants in the event which significantly influences the interpretation of a text. The objective of this study is to examine the positioning regarding Hamas in a parallel corpus-based Israel-Palestine conflict. The corpus comprises 160 articles that have been translated from English to Indonesian. The researcher applied the evaluative model proposed by Pan and Liao (2020), that integrated CDA (Fairclough, 2013), Appraisal Theory (Martin & White, 2005), and Narrative Theory (Baker, 2006). It was found that the translators intentionally and carefully (re)positioned of Hamas by implementing a discursive strategy called redacted labelling in their actual activities. This can be done by omitting, adding, softening, and even strengthening the word construction embedded in these elements. The activities were motivated by the political stance of the news organization as determined by its official identity, media discourse counterpoints, the situation of the political of Indonesia toward the conflict, and their expectations of the reaction of the target audience. Examining news translation using CDA adds to translation theory by providing a critical perspective on how non-linguistic elements like ideology, power, and culture influence the translation process. It provides a more in-depth understanding of the translator's position as an agent who translates meanings, values, and worldviews as well as words.